Work Discipline Implementation Strategy to Improve the Productivity of Daily Contract Employees in the Traffic Division of the Semarang City Transportation Agency - Ady Hermawan; Adhitya Yoga Prasetya (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2024)
This study investigates the implementation strategy of work discipline as a means to improve the productivity of daily contract employees in the Traffic Division of the Semarang City Transportation Agency. Work discipline is a critical component of human resource management that influences performance effectiveness and organizational efficiency. The research applies a qualitative descriptive approach using interviews, observation, and document analysis to examine discipline practices, attendance data, and managerial supervision. The results show that effective disciplinary implementation—through structured supervision, reward and punishment systems, continuous coaching, and welfare enhancement—significantly improves employee productivity. Leadership quality, motivation, and consistent policy enforcement emerge as primary determinants of disciplined behavior. The study concludes that establishing a fair and transparent disciplinary system can foster accountability, punctuality, and professional service delivery among public employees.